ANALISIS RISIKO USAHATANI BAWANG MERAH - Yoel Melsaro Larosa; Ridho Victory Nazara; Kurnia Selekta Etika Harefa; Putra Hidayat Telaumbanua; Helmin Parida Zebua; Dian Agung Sanora Laia; Natalia Kristiani Lase; Yarman Gulo (Jurnal Sapta Agrica, 2025)
This study aims to analyze the level of production and price risk in red onion farming, as well as to examine the behavior of red onion farmers in Tiganderket Village, Tiganderket Subdistrict, Karo Regency. The main focus of the study is to understand the extent of the risks faced by farmers in red onion production and how their decisions and willingness to take risks influence farming practices. The sample was determined using a census method, where the entire population of red onion farmers in the study area was used as respondents, totaling 15 individuals. Primary data were collected through surveys and direct interviews, ensuring that the information reflects the actual conditions in the field. Data analysis was conducted using multiple linear regression to determine the influence of several variables on production and price risk levels. The results showed that the production risk in red onion farming in Tiganderket Village is considered high, indicated by a coefficient of variation of 0.52, which exceeds the threshold of 0.5. Conversely, the price risk is relatively low, with a coefficient of variation of 0.02, well below the threshold. Furthermore, the behavior of farmers in facing risks is also considered high; all respondents, 100%, demonstrated a willingness to take risks in red onion farming practices. These findings indicate that although red onion production carries a high level of risk, farmers still exhibit proactive behavior and a willingness to make risky decisions, while price fluctuation risks are relatively low. Therefore, economically, red onion farming can still be carried out with a reasonable degree of certainty. These results can serve as a basis for developing agricultural strategies and supportive policies for red onion farmers in Karo Regency.